PUBLIC AND ANIMAL HEALTH IMPLICATIONS OF BLOOD FEEDING VECTORS - Kapaldo, Nathaniel (My University, 2017)
Arthropod vectors are capable of transmitting pathogens (e.g., bacteria, helminths, protozoa, and viruses) between mammals which may result in numerous diseases affecting both human and animal populations. Arthropod transmitted pathogens are responsible for 17% of infectious diseases and 20% of emerging infectious diseases worldwide. Recent emergence of traveler-associated vector-borne diseases (VBD) in North America (e.g., Chikungunya and Zika viruses) affecting human health, attention to vectors and to the pathogens that they transmit has greatly increased. Effective and efficient monitoring of vector populations is the logical first step in understanding disease transmission risk and avenues for initiating vector control. At military installations, service dogs and handlers employed by the United Stated (US) Army, are potentially at an increased risk from VBDs due to protracted entomological exposure during their work and training. These VBDs pose significant risk to the health and welfare of military working dogs (MWD) and additional risk to military personnel through both zoonotic transmission (i.e., animal to human pathogen transmission) and through MWDs acting as pathogen reservoirs able to infect local arthropod vector populations. Monitoring MWD kennel and training areas is currently not employed by the US military and may benefit both the canine handler’s and MWD health. Within zoos, risk of VBD transmission is potentially increased due to unique biodiversity and static animals within customized enclosures. Zoos provide a great diversity of microhabitats that are capable of establishing both highly abundant and diverse populations of disease vectors (e.g., mosquitoes and biting flies). The impact of high biting insects populations on animals kept static in enclosures is unknown; however, recent research eludes to significant entomological risk. Risk may be in the form of both increased risk of disease transmission and increased distress due to significant biting pressures experienced by zoo animals. There is great need for an effective and efficient vector monitoring program that may be fitted to unique zoo environments and may be used annually. Information gained may guide our efforts making future monitoring and control recommendations.
Keywords: mosquito surveillance; vector borne disease; zoonotic; zoo; biting pressure; animal welfare